Media, domocracy, and government action: Prevention vs. palliation in the time of cholera - Chongwoo Choe; Paul A. Raschky (Osaka University, Institute of Social and Economic Research (ISER), 2011)
This paper studies how media and democracy influence government action taken before and after a natural disaster. The key elements in this relationship are the media's role as the provider of information to voters about government action and the quality of democracy that pertains to how relevant election results are. We show that more media activity and more democratic institutions both contribute positively to the government's palliative effort after the disaster. However, the effects of media and democracy on the government's preventive effort before the disaster are negative. We provide empirical evidence based on major cholera epidemics around the world, which lends some support to these hypotheses.
Keywords: D23; H40; L82; 330; media; democracy; corruption; natural disaster; Epidemie; Katastrophe; Kommunikationsmedien; Öffentliche Meinung; Humanitäre Hilfe; Welt